Comunicación en consejo genético - Cruzado, Juan Antonio; Olivares, María Eugenia (Psicooncología, 2005)
Cancer genetic counseling is based on communication process. Oncologist and other health professionals involved in genetic counselling must be well-trained in communication skills. Optimal information in cancer genetic counseling must answer the following questions: What should be informed?, Who should be informed?, Who must inform?, When should information be given?, How we should inform?. The information content should cover as much objective as subjectives/emocional and social aspects of genetic counseling, according the common sense model. The participants and its relatives authorized are to whom the information should be delivered, taking in account personal characteristics,needs and coping styles. The responsible doctor should inform about objective and medical aspects, and psychologist should inform about subjective, emotional and social aspects. The importance of coherence in the information between all professionals involved in genetic counselling is underscored.Information should be delivered in small dose of sequential form, according to the process phase so understanding and recall could be facilitated. With regard to how should the information be given, it is exposed an adaptation of the SPIKES guidelines for cancer genetic counseling, which underscores the importance on keep in mind the information needs,understanding confirmation, attention to personal concerns and emotional support. We remark that communication among different family members is very important to help participants to iniciate genetic counselling process and decision making on prophylactic measures.Finally, it is proposed to research the contents and processes of communication that sanitary professionals carry out at genetic counseling.